Performance variables and nutritional status analysis from Moroccan professional and adolescent football players during the competition period: a descriptive study - Mourad Oukheda; Halima Lebrazi; Abdelfettah Derouiche; Anass Kettani; Anass Kettani; Rachid Saile; Hassan Taki (Frontiers in Sports and Active Living)
IntroductionNutrition plays an integral role in optimizing football players’ performance during training sessions and matches and maintaining their overall health throughout the season. This study aimed to evaluate how well the dietary practices of professional and adolescent football players in Morocco during the competitive period met international macronutrient recommendations, and to explore the relationship between their nutritional status and aerobic performance, as measured by the Yo-Yo IRL1 test.MethodsA total of 277 footballers from Morocco's professional league, “Botola-Pro”, were monitored over a seven-day (training microcycle) during the competitive period. The dietary intake was assessed through self-reported methods and 24-hour recalls. Relevant body composition was measured with bioelectrical impedance (BI), and aerobic performance was evaluated using the Yo-Yo IR test.ResultsThe results indicated significant variations in performance and nutritional status across different categories and age groups. The nutritional status of the players didn't match the UEFA recommendations (p < 0.001). We found that higher intake levels of carbohydrates and proteins were positively correlated with the total distance covered by the players (p < 0.001, r = 0.63, R2 = 0.4 for carbohydrates; p < 0.001, r = 0.59, R2 = 0.35 for proteins). Conversely, a higher proportion of energy derived from fats in the diet was negatively correlated with the distance covered (p < 0.001, r = −0.64, R2 = 0.41).ConclusionThese findings suggest that optimizing carbohydrates and protein intake while managing fat consumption is crucial for enhancing sporting performance. This information is essential for tailoring training programs and nutritional regimens based on the competition level.